Clinical outcome analysis of frozen-thawed embryo transfer on Day 7 - Liu, Xinmi; Lou, Hua; Zhang, Junwei; Du, Mingze; Du, Yulin; Wu, Shanshan; Guan, Yichun; Liu, Jing (Frontiers in Endocrinology, 2022)
Objective: To investigate the clinical outcomes of Day 7 (D7) frozen-thawed embryo transfer (FET) and to provide a reference value for clinical work. Methods: This was a retrospective cohort study. Patients undergoing FET cycles in the Reproductive Medicine Center of the Third Affiliated Hospital of Zhengzhou University between December 2015 and January 2021 were included. According to the developmental stage of the embryos at transfer, the embryos were divided into three groups: Day (D) 5, D6 and D7 blastocysts. Group D7 was compared with Groups D5 and D6. Simultaneously, the preimplantation genetic testing (PGT) and non-PGT cycles in Group D7 were analyzed and compared. The main outcomes were the clinical pregnancy, live birth and miscarriage rates. The secondary outcomes were the implantation and euploidy rates. Results: In total, 5945, 4094 and 137 FET cycles were included in the D5, D6 and D7 groups, respectively. The clinical pregnancy rate was significantly lower in Group D7 than in Groups D5 (13.9% vs 62.9%, P <0.001) and D6 (13.9% vs 51.4%, P <0.001). Additionally, the live birth rate was significantly lower in Group D7 than in Groups D5 (7.3% vs 50.7%, P <0.001) and D6 (7.3% vs 40.5%, P <0.001). However, the miscarriage rate was significantly higher in Group D7 than in Groups D5 (47.4% vs 18.2%, P =0.001) and D6 (47.4% vs 20.6%, P =0.004). The clinical pregnancy and live birth rates for D7 blastocysts were significantly higher in the PGT group than in the non-PGT group (41.7% vs 13.9%, P=0.012; 33.3% vs 7.3%, P =0.003). Conclusions: D7 blastocyst transfer can yield a live birth rate that is lower than that for D5 and D6 blastocysts but has value in transfer. PGT for D7 blastocysts may reduce the number of ineffective transfers and improve the outcome of D7 blastocyst transfer, which can be performed according to a patient's situation.